A high-speed imaging and modeling study of dendrite fragmentation caused by ultrasonic cavitation - Shu, D; Sun, B; Mi, J; Grant, P (2012)
The dynamic behavior of ultrasound-induced cavitation bubbles and their effect on the fragmentation of dendritic grains of a solidifying succinonitrile 1 wt pct camphor organic transparent alloy have been studied experimentally using high-speed digital imaging and complementary numerical analysis of sound wave propagation, cavitation dynamics, and the velocity field in the vicinity of an imploding cavitation bubble. Real-time imaging and analysis revealed that the violent implosion of bubbles created local shock waves that could shatter dendrites nearby into small pieces in a few tens of milliseconds. These catastrophic events were effective in breaking up growing dendritic grains and creating abundant fragmented crystals that may act as embryonic grains; therefore, these events play an important role in grain refinement of metallurgical alloys. © 2012 The Minerals, Metals and Materials Society and ASM International.